Study of clinico-epidemiological risk factors associated with enteric encephalopathy in children - Panda, Prateek Kumar; Panda, Kalpana (International Journal of Contemporary Pediatrics, 2018)
Background: Although relatively less prevalent, yet enteric encephalopathy is one of the severe complications of enteric fever, which often remains underdiagnosed and undertreated. Data on enteric encephalopathy in children in Indian literature is scarce. Methods: Current retrospective study was conducted by reviewing the case records of all children admitted with enteric fever between January 2013 and December 2017 in a tertiary health care center. Then the clinical characteristics and laboratory parameters of the subgroup with and without enteric encephalopathy was compared. Results: Out of the 295 children with enteric fever, 19 children (6.4%) had evidence of enteric encephalopathy during hospital stay. Common clinical presentations were altered sensorium, gait instability, seizure, irrelevant talking and behavioral abnormality. All the children survived after being treated with intravenous dexamethasone along with antibiotics. As compared to the group without encephalopathy, this group had more children with lower socioeconomic status, delayed treatment initiation, malnutrition, higher respiratory rate and heart rate, lower leukocyte and platelet count, higher incidence of hepatic dysfunction, higher Salmonella typhi H and O agglutinin titer. Conclusions: Appropriate clinical suspicion for early diagnosis, timely treatment with dexamethasone and good supportive care is likely to cause favorable outcome in children with enteric encephalopathy.